Analysis of a chemically reactive MHD flow with heat and mass transfer over a permeable surface - Fenuga, Olugbenga John; Aroloye, S.J.; Popoola, Amos Oladele (Zielona Góra: Uniwersytet Zielonogórski)
This paper investigates a chemically reactive Magnetohydrodynamics fluid flow with heat and mass transfer over a permeable surface taking into consideration the buoyancy force, injection/suction, heat source/sink and thermal radiation. The governing momentum, energy and concentration balance equations are transformed into a set of ordinary differential equations by method of similarity transformation and solved numerically by Runge-Kutta method based on Shooting technique.
Keywords: heat transfer; mass transfer; chemically reactive MHD flow; permeable surface